2017
DOI: 10.1242/dev.155176
|View full text |Cite
|
Sign up to set email alerts
|

Dlx5-FGF10 signaling cascade controls cranial neural crest and myoblast interaction during oropharyngeal patterning and development

Abstract: Craniofacial development depends on cell-cell interactions, coordinated cellular movement and differentiation under the control of regulatory gene networks, which include the distal-less (Dlx) gene family. However, the functional significance of in patterning the oropharyngeal region has remained unknown. Here, we show that loss of leads to a shortened soft palate and an absence of the levator veli palatini, palatopharyngeus and palatoglossus muscles that are derived from the 4th pharyngeal arch (PA); however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 35 publications
(48 reference statements)
2
34
0
Order By: Relevance
“…5 B'', C''). These observations reinforce the notion that cephalic myogenic precursors require Dlx5/6dependent morphogenetic instructions from NCCs for proper jaw muscle patterning and differentiation 38 .…”
Section: Dlx5/6 Expression In Neural Crest Cells Is Required For Propsupporting
confidence: 85%
“…5 B'', C''). These observations reinforce the notion that cephalic myogenic precursors require Dlx5/6dependent morphogenetic instructions from NCCs for proper jaw muscle patterning and differentiation 38 .…”
Section: Dlx5/6 Expression In Neural Crest Cells Is Required For Propsupporting
confidence: 85%
“…However, other muscles, including the levator veli palatine, palatopharyngeal, and palatoglossal, are innervated by branches of the vagus (CNX) nerve, indicative of a more caudal embryonic origin (Edgeworth, ; Michailovici et al, ). Tracing studies using Dlx5 as a marker found that NCr cells from BA4 move into the developing soft palatal shelves and form a scaffolding necessary for the morphogenesis of their accompanying myoblasts (Grimaldi, Parada, & Chai, ; Sugii et al, ).…”
Section: Partnering Myoblasts With Neural Crest Cellsmentioning
confidence: 99%
“…In vitro, BMP and WNT inhibit the proliferation and differentiation of myoblasts, which can be rescued by the addition of noggin, gremlin, or FRZB (Tzahor et al 2003). Simultaneously, Dlx5 is expressed by SCX-positive precursors (Sugii et al 2017). Dlx5 knockout mouse embryos in this study show reduced fibroblast growth factor 10 (FGF10) expression and impaired branchiomeric muscle formation.…”
Section: Molecular Regulation Of Branchiomeric Muscle Developmentmentioning
confidence: 66%
“…The orofacial muscles include the muscles of mastication, the muscles of cheeks and lips, the soft palate muscles, the suprahyoid muscles, and the tongue muscles (Le Reverend et al 2014). These muscles develop from the mesoderm of the pharyngeal arches and the occipital somites (Sugii et al 2017;Chang and Kioussi 2018). The muscles of the trunk and limbs develop from the thoracic and lumbal somites, respectively (Chang and Kioussi 2018).…”
Section: Introductionmentioning
confidence: 99%